Evolution of Sustainable Waste Management Models in the Tourism Industry: A Systematic Literature Review - Alim, Azmi Kautsar; Intan, Amalia Juliana Monika; Widiyanti, Rikantini; Noor, Any Ariani (Journal of Tourism, Hospitality and Travel Management, 2026)
This study advances tourism waste scholarship by introducing the Socio-Technical Regenerative Tourism Waste Model (STR-TWM), a framework that maps the transition from linear, disposal-oriented practices toward circular, technology-enabled, and socially embedded systems. Despite the growing urgency of waste challenges in tourism, existing literature remains fragmented, often focusing on isolated technical or policy solutions. Through a systematic literature review (SLR) of 47 peer-reviewed journal articles (2020–2025) following PRISMA guidelines, this study examines the evolution of Sustainable Waste Management (SWM) models, particularly within the geographically complex context of Southeast Asia. Findings identify a paradigm shift from disposal-centric approaches toward hybrid models that integrate Circular Economy (CE) principles, Industry 4.0-based smart technologies, and stakeholder-integrated governance. The proposed STR-TWM conceptualizes SWM as a regenerative system in which digital transparency enables circular material flows, anchored within community-based governance structures. While policy incentives and technological affordability drive this transition, it remains constrained by archipelagic logistical fragmentation and behavioral compliance gaps. Managerially, the study provides strategic guidance for policymakers and destination managers seeking to operationalize zero-waste pathways. By synthesizing diverse technological and social subsystems, this review offers a coherent roadmap for advancing regenerative tourism systems.